The animated worlds of Piercing I, iMirror, and RMB City: Decoding postsocialist reality through virtual spaces. Issue 2 (4th May 2019) - Zhang, Linda C.
Abstract: Realist aesthetics has dominated critical discussion of postsocialist Chinese cultural production. This paper argues that contemporary Chinese animated media subverts the logic of realism by enacting virtual spaces, and in turn, hosting abject scenarios of socio-economic marginalization and even fantastic illusions of hyper-consumerism. Liu Jian's (2010 ) film Piercing I (刺痛我), depicts the plight of marginalized migrant workers in the big city and creates an absurd, exaggerated, and malnourished vision of a place where human characters lose their lives in a brutal, capitalist world. In contrast, multimedia artist's Cao Fei's (2007 ) virtual documentary, iMirror, joyfully explores digital creation in its colorful illusion of social mobility, following Cao Fei's avatar as she explores the virtual platform of Second Life – an exploration that continues in her later digital city project, RMB City (2008–2011). Online and in the gallery, iMirror and RMB City invite user engagement and creativity with a hyper-consumerist and dream-like space. Despite their divergent visions, the animated spaces created in these projects provide an interface to decipher the reality of the world in a mediated manner, but they are also marked by an ideological ambivalence towards the experience of alienation in postsocialist urban life.